2014
DOI: 10.1098/rspa.2013.0832
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced load-carrying capacity of hairy surfaces floating on water

Abstract: Water repellency of hairy surfaces depends on the geometric arrangement of these hairs and enables different applications in both nature and engineering. We investigate the mechanism and optimization of a hairy surface floating on water to obtain its maximum load-carrying capacity by the free energy and force analyses. It is demonstrated that there is an optimum cylinder spacing, as a result of the compromise between the vertical capillary force and the gravity, so that the hairy surface has both high load-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…As expected based on the results for a single horizontal cylinder in Section 3.2, the precise value of the contact angle plays only a minimal role, provided that θ > π/2. Xue et al (2014) also found that, when the separation between the hairs becomes very small, d c , the total load that can be supported by the raft becomes insensitive to the value of d. (This agrees with the generalization of Archimedes' principle, as this force is simply the weight of liquid displaced.) However, the authors also observed that there is in fact an optimum value of d, www.annualreviews.org • Floating Versus Sinking at which the load supported is maximized.…”
Section: Hairy Legssupporting
confidence: 55%
See 3 more Smart Citations
“…As expected based on the results for a single horizontal cylinder in Section 3.2, the precise value of the contact angle plays only a minimal role, provided that θ > π/2. Xue et al (2014) also found that, when the separation between the hairs becomes very small, d c , the total load that can be supported by the raft becomes insensitive to the value of d. (This agrees with the generalization of Archimedes' principle, as this force is simply the weight of liquid displaced.) However, the authors also observed that there is in fact an optimum value of d, www.annualreviews.org • Floating Versus Sinking at which the load supported is maximized.…”
Section: Hairy Legssupporting
confidence: 55%
“…Indeed, as r hair / c → 0, the importance of this optimum diminishes (i.e., the maximum supported load becomes closer to that supported by close-packed hairs, d / c → 0). The numerical results of Xue et al (2014) show that d optimal ∼ Bo 1/3 hair where Bo hair = (r hair / c ) 2 is the Bond number of the hairs (see Figure 5c). This simple scaling result is valid over a remarkably large range of Bond numbers and is not, to my knowledge, understood.…”
Section: Hairy Legsmentioning
confidence: 93%
See 2 more Smart Citations
“…[6][7][8][9][10][11] Slip lengths on smooth hydrophobic surfaces have been reported at the nanoscale, and can reach as high as tens or hundreds of microns 12,13 when hydrophobic surfaces are rendered superhydrophobic by manufacturing micro/nano structures. [14][15][16][17][18] This is attributed to the high area fraction of shear-free liquid-air interfaces at solid surfaces.…”
Section: Introductionmentioning
confidence: 97%